2007
DOI: 10.1038/sj.cdd.4402197
|View full text |Cite
|
Sign up to set email alerts
|

Human lipodystrophies linked to mutations in A-type lamins and to HIV protease inhibitor therapy are both associated with prelamin A accumulation, oxidative stress and premature cellular senescence

Abstract: Lipodystrophic syndromes associated with mutations in LMNA, encoding A-type lamins, and with HIV antiretroviral treatments share several clinical characteristics. Nuclear alterations and prelamin A accumulation have been reported in fibroblasts from patients with LMNA mutations and adipocytes exposed to protease inhibitors (PI). As genetically altered lamin A maturation also results in premature ageing syndromes with lipodystrophy, we studied prelamin A expression and senescence markers in cultured human fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
241
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(267 citation statements)
references
References 44 publications
18
241
2
1
Order By: Relevance
“…13 Accordingly, the presence of prelamin A has been observed in lipoatrophic abdominal scAT from HIV-infected patients receiving a protease inhibitorbased therapeutic regimen. 11 We and others have previously reported the presence of mitochondrial abnormalities in cells and/or lipoatrophic adipose tissue from patients with LMNA mutations or HIV infection 11,14 -16 Moreover, patients with mutations in mitochondrial DNA (mtDNA)-encoded tRNA Lys can develop dorsocervical non-encapsulated fat masses, [17][18][19] which suggests that mitochondrial dysfunction could also have a role in LMNA-and HIV-linked lipodystrophies. Thus far, histologic features of LMNA-mutated scAT have not been reported, with the exception of an ultrastructural analysis that revealed nuclear alterations in some lipoatrophic adipocytes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…13 Accordingly, the presence of prelamin A has been observed in lipoatrophic abdominal scAT from HIV-infected patients receiving a protease inhibitorbased therapeutic regimen. 11 We and others have previously reported the presence of mitochondrial abnormalities in cells and/or lipoatrophic adipose tissue from patients with LMNA mutations or HIV infection 11,14 -16 Moreover, patients with mutations in mitochondrial DNA (mtDNA)-encoded tRNA Lys can develop dorsocervical non-encapsulated fat masses, [17][18][19] which suggests that mitochondrial dysfunction could also have a role in LMNA-and HIV-linked lipodystrophies. Thus far, histologic features of LMNA-mutated scAT have not been reported, with the exception of an ultrastructural analysis that revealed nuclear alterations in some lipoatrophic adipocytes.…”
mentioning
confidence: 99%
“…We and others have demonstrated that FPLD2 and metabolic laminopathies are associated with an abnormal accumulation of prelamin A, possibly due to misrecognition of the mutated protein by Zmpste24. 10,11 That LMNA mutations can lead to lipoatrophy in most scAT depots, but to lipohypertrophy in the faciocervical area, remains poorly understood but could be linked to differences in fat depot physiologic features. It has been suggested that prelamin A accumulation may elicit different effects in body fat areas, depending on the level of local activation of the adipogenic factor peroxisome proliferator-activated receptor-␥ (PPAR␥).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, they can have an iatrogenic origin, as in HIV patients treated with protease inhibitors. Most molecules of this class inhibit ZMPSTE24 function, resulting in the blockage of prelamin A maturation and its accumulation in nuclei, leading to clinical manifestations of lipodystrophy syndrome (Béréziat et al., 2011; Caron et al., 2007; Coffinier et al., 2008; Miranda et al., 2007). …”
Section: Lamins and Laminopathiesmentioning
confidence: 99%
“…There is a subtle balance between the production and removal of the different ROS molecules to maintain their intracellular concentration at a physiological level. Any perturbation to this fragile steady-state that increases intracellular ROS provokes oxidative stress, a phenomenon associated with the natural aging process, as well as various multispectrum diseases including cancer and laminopathies (Harman 1956;Naderi et al 2006;Moylan and Reid 2007;Caron et al 2007;Salmon et al 2010;Sieprath et al 2012). …”
Section: Intracellular Ros Metabolismmentioning
confidence: 99%